Robin Wood on the horror film : collected essays and reviews - Wood, Robin, 1931-2009 (Contemporary approaches to film and media series., 2018)
Robin Wood - one of the foremost critics of cinema - has laid the groundwork for anyone writing about the horror film in the last half-century. Robin Wood on the Horror Film: Collected Essays and Reviews compiles over fifty years of his groundbreaking critiques.